2013
DOI: 10.1038/nmat3819
|View full text |Cite
|
Sign up to set email alerts
|

A nanoparticle-based strategy for the imaging of a broad range of tumours by nonlinear amplification of microenvironment signals

Abstract: Stimuli-responsive nanomaterials are increasingly important in a variety of applications such as biosensing, molecular imaging, drug delivery and tissue engineering. For cancer detection, a paramount challenge still exists in search of methods that can illuminate tumors universally regardless of their genotypes and phenotypes. Here we capitalized on the acidic, angiogenic tumor microenvironment to achieve broad detection of tumor tissues in a wide variety of mouse cancer models. This was accomplished using ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
573
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 707 publications
(580 citation statements)
references
References 35 publications
(37 reference statements)
5
573
0
2
Order By: Relevance
“…Second, the stimuli that were used to trigger size shrinkage previously were either by enzyme or UV light, whose applicability, to a certain extent, would be restricted to only a subset of cancer types owing to either the heterogeneous expression levels of target enzymes in a specific cancer type or the superficial penetration depth of UV light (14). In contrast, we used acidic extracellular pH, a more general hallmark of the microenvironment of most solid tumors (36,48), as the stimulus to activate the release of small particles at tumor sites. This endows our strategy with much broader specificity and applicability, which has been partially justified by the superior antitumor activities in multiple tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the stimuli that were used to trigger size shrinkage previously were either by enzyme or UV light, whose applicability, to a certain extent, would be restricted to only a subset of cancer types owing to either the heterogeneous expression levels of target enzymes in a specific cancer type or the superficial penetration depth of UV light (14). In contrast, we used acidic extracellular pH, a more general hallmark of the microenvironment of most solid tumors (36,48), as the stimulus to activate the release of small particles at tumor sites. This endows our strategy with much broader specificity and applicability, which has been partially justified by the superior antitumor activities in multiple tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…30 Previous studies reported that hypoxic regions in the tumors are more acidic. 31 Thus, the abovementioned pH-responsive liposomes can obtain the surface positive charge density under tumor hypoxic conditions and will improve the uptake efficiency by tumor cells. It has been demonstrated that the nitro group of nitroimidazoles can be converted to an amino group through a series of selective bioreductions under hypoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, nanomaterials have been developed as probes for fluorescent, optical, Raman, and magnetic resonance imaging of the tumor (20-23). The use of dual-emissive materials or stimuli-responsive nanomaterials has further advanced the imaging modality to the molecular level by conferring the ability to monitor subcellular and microenvironment changes, such as hypoxia or pH transitions (24,25). Similarly, tumor-activatable nanoparticles were used to detect metastasis and residual tumor (26).…”
mentioning
confidence: 99%